How Perceived Service Quality Drives Customer Retention: Evidence of Partial Mediation by Customer Trust in B2B Logistics - Budi Prakoso (Universitas Pendidikan Indonesia, 2025)
Customer retention constitutes a critical strategic outcome in B2B logistics, where relationship continuity depends on both service performance and relational confidence. This study investigates the effect of perceived service quality on customer retention, with customer trust positioned as a mediating variable, in the enterprise logistics context of PT Pos Indonesia. A quantitative explanatory approach was employed using cross-sectional survey data collected from 200 enterprise customers. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that perceived service quality exerts a positive and significant effect on customer trust and customer retention, while customer trust also has a positive and significant effect on customer retention. Furthermore, customer trust significantly mediates the relationship between perceived service quality and customer retention. Since both the direct and indirect effects remain significant, the mediating role of customer trust is classified as partial mediation. These results demonstrate that customer retention in B2B logistics is shaped through two complementary mechanisms: the direct operational value of superior service quality and the indirect relational pathway established through trust. The study contributes to the service and relationship marketing literature by clarifying this dual-pathway mechanism in underexplored enterprise logistics setting.